Expansion of myeloid-derived suppressor cells in the peripheral blood of patients with ankylosing spondylitis - A. Yu. Morenkova (SPb RAACI, 2021)
Expansion of myeloid-derived suppressor cells (MDSCs) due to impaired differentiation of myeloid progenitor cells under conditions of inflammation was described in a number of autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus, and type 1 diabetes mellitus. Studying the role of MDSCs in ankylosing spondylitis is an important issue, given that increased concentration of proinflammatory mediators in this pathology can also cause myelopoiesis disorders. The aim of present work was to study the quantitative content of MDSC subpopulations in patients with different clinical phenotypes and activity of AS. 37 patients, including 10 patients without peripheral skeletal lesions (axial form) and 27 patients with simultaneous lesions of spine and peripheral joints (peripheral form) were recruited into the study. The control group consisted of 32 age/sex-related healthy donors. Evaluation of granulocytic (LinHLA-DRCD33+CD66b+; G-MDSC), monocytic (CD14+HLA-DRlow/-; M-MDSC) and early-stage MDSCs (LinHLA-DRCD33+CD66b- ; E-MDSC) was performed using corresponding antibodies (BD Biosciences, USA) in the population of peripheral blood mononuclear cells by flow cytometry. In general, the AS patients were characterized by an increased relative and absolute amount of M-MDSC (p = 0.00002 and p = 0.00003, respectively) and G-MDSC (p = 0.0002 and p = 0.0006, respectively). Patient gender, age, and HLA-B27 expression did not significantly affect the content of these cells in peripheral blood. An increase in the median values of M-MDSC was detected both in patients with axial (Ме 5.0 (3.2-6.3) versus 2.4 (1.7-3.5) %; p = 0.001) and peripheral form (Ме 5.0 (3.0-7.0) versus 2.4 (1.7-3.5) %; p = 0.0002) AS. At the same time, the G-MDSC expansion was observed only in patients with involvement of peripheral joints (Ме 0.16 (0.07-0.3) % versus 0.05 (0.04-0.09) %; p = 0.0001). The relative contents of E-MDSC, M-MDSC and G-MDSC in the axial form of AS was in direct correlation with the activity of the disease (R = 0.58, p = 0.02; R = 0.73, p = 0.08 and R = 0.65 p = 0.04, respectively). This relationship was not observed in peripheral form of AS. The data obtained suggest a potential involvement of MDSCs in pathogenesis and phenotypic heterogeneity of AS. Simultaneously, the revealed direct correlation between the MDSC contents and the disease activity suggests a decrease in suppressive activity and/or appearance of pro-inflammatory activity in MDSC, thus requiring further research in the field.